2012
DOI: 10.1148/radiol.12112245
|View full text |Cite
|
Sign up to set email alerts
|

Brain Hemodynamic Changes Associated with Chronic Cerebrospinal Venous Insufficiency Are Not Specific to Multiple Sclerosis and Do Not Increase Its Severity

Abstract: Purpose:To investigate the relationship between chronic cerebrospinal venous insufficiency (CCSVI) and cerebral hemodynamic parameters and to disclose any possible involvement in the pathophysiology of multiple sclerosis (MS). Materials and Methods:The study was approved by the institutional review board, and written informed consent was obtained from all participants. The diagnosis of CCSVI was assigned by using specific color Doppler ultrasonographic criteria. Cerebral blood volume (CBV), cerebral blood flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 29 publications
(30 reference statements)
0
37
0
2
Order By: Relevance
“…Even those DS studies which detected a significant difference for CCSVI diagnosis between MS patients and the controls, reported a substantially lower prevalence than was originally reported [30,31,83,88,90,92-94,98,99]. …”
Section: Noninvasive Imaging Modalitiesmentioning
confidence: 61%
“…Even those DS studies which detected a significant difference for CCSVI diagnosis between MS patients and the controls, reported a substantially lower prevalence than was originally reported [30,31,83,88,90,92-94,98,99]. …”
Section: Noninvasive Imaging Modalitiesmentioning
confidence: 61%
“…[15][16][17][18]31 MR imaging venographic data have been mixed, with the sonographic findings not being replicated. 20,32 A combined sonography and MRV study 21 was not able to replicate the findings in 40 patients with MS. A recent MR imaging study by Garaci et al 33 demonstrated no significant specific interaction between the presence of chronic cerebrospinal venous insufficiency and MS in measured hemodynamic changes of mean transit time, cerebral blood flow, or volume. We undertook a study with experienced vascular sonographers, a vascular interventional neuroradiologist, and an MS neurologist and were unable to find a single case on sonography fulfilling the criteria of Zamboni et al 9 for chronic cerebrospinal venous insufficiency.…”
Section: Discussionmentioning
confidence: 94%
“…29 Other possible underlying mechanisms were later suggested. Recent studies using MRI or metabolic PET studies 30,31 have highlighted a reduction of arterial inflow within the damaged white matter, particularly the periventricular normal-appearing white matter, 32,33 extending to the cerebral cortex and deep gray matter. Cerebral hypoperfusion in MS patients was mainly assumed to be secondary to reduced metabolic demand due to axonal degeneration.…”
Section: Venous Flowsmentioning
confidence: 99%